2019
DOI: 10.3390/f11010013
|View full text |Cite
|
Sign up to set email alerts
|

Local Preferences for Shea Nut and Butter Production in Northern Benin: Preliminary Results

Abstract: Shea products in Benin (West Africa) are produced in a low-developed agroindustry, but they are estimated to be the country’s third largest export. The nut harvesting and quality guaranteeing in the butter process can only be achieved through improvements in the value chain, thus making it more attractive for stakeholders. The aim of this paper is to provide keys to a better product valorization, obtain a significant increase in household incomes based on shea butter marketing opportunities, and offer competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
(27 reference statements)
0
15
0
Order By: Relevance
“…Gender influence could be perceived in the processing of shea nuts where men were not involved. Along the same lines, Agúndez et al [ 31 ] suggested that the development of shea resource management and conservation programs should include ethnic preferences and consider gender, to avoid reducing women’s profits in the shea butter local market.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender influence could be perceived in the processing of shea nuts where men were not involved. Along the same lines, Agúndez et al [ 31 ] suggested that the development of shea resource management and conservation programs should include ethnic preferences and consider gender, to avoid reducing women’s profits in the shea butter local market.…”
Section: Discussionmentioning
confidence: 99%
“…Gnanglè [ 30 ] reported that shea is an economically, socially, and culturally important tree for northern and central Benin. In addition, Agundez et al [ 31 ] have recently studied local preferences for shea nut and butter production in Northern Benin. These authors found that the willingness to pay for a specific quality of nuts/butter depends on a number of their physical attributes.…”
Section: Introductionmentioning
confidence: 99%
“…Gender in uence could be perceived in processing of shea nuts where men were not involved. Along the same lines, Agúndez et al, [31] suggested that the development of shea resources management and conservation programs should include ethnic preferences and consider gender, to avoid reducing women's pro ts in the shea butter local market.…”
Section: Characterization Of Shea Morphotypesmentioning
confidence: 99%
“…In addition. Agundez et al [31] have recently studied local preferences for shea nut and butter production in Northern Benin. To date, no study have been undertaken to assess local knowledge on shea morphotypes traits and how they can be used in shea cultivars development.…”
Section: Introductionmentioning
confidence: 99%
“…Vlad et al [25] studied and promoted blackberry as a traditional nutraceutical food resource from an area with high anthropogenic impact. Agúndez et al [26] studied local preferences for production of shea nut and butter in Northern Benin. Darr et al [27] mapped the diversity of baobab (Adansonia digitata L.) products in Malawi by studying the preferences of consumers and examining the major attributes on their market price.…”
mentioning
confidence: 99%